Upaya Guru Dalam Meningkatkan Motivasi Hafalan Al-Qur’an Pada Program Tahfidz Belia - Yusuf, Nur Alawiyah Kharisma; Formen, Ali; Sunarso, Ali; Pranoto, Yuli Kurniawati Sugiyo (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2025)
Memorization is an activity that requires motivation, perseverance, habit formation, and appropriate guidance from an educator. In early childhood, enthusiasm for memorization tends to be unstable, requiring continuous support. Based on these conditions, this study was conducted to examine the role of tahfidz teachers in increasing the motivation of students to memorize in the Tahfidz Belia Program at the Bustanul Qur'an Al-Asror Islamic Boarding School. The study applied a qualitative approach with data collection methods in the form of observation, interviews, and documentation. Primary data was obtained through direct observation and interviews, while secondary data was obtained from documents and records of the students' memorization progress. The results of the study show that tahfidz teachers play a significant role in guiding students during the memorization process. Teachers not only act as motivators, but also as mentors, inspirers, and evaluators who systematically monitor memorization progress. Various strategies were implemented to increase motivation, including setting memorization targets, individualized approaches, rewards, and structured tahfidz routines. This approach proved effective in increasing the students' discipline and enthusiasm for learning. The study also identified inhibiting factors, such as young age, lack of focus, and peer influence. These findings are expected to serve as a reference for educational institutions in developing more effective tahfidz programs.